PENGARUH APLIKASI PSEUDOMONAS FLUORESCENS P60 TERHADAP MUTU PATOLOGIS, MUTU FISIOLOGIS, DAN PERTUMBUHAN BIBIT PADI IR 64 - Lisa Navitasari; Loekas Soesanto; Ahadiyat Yugi Rahayu (Universitas Lampung, 2013)
Effect of Pseudomonas fluorescens P60 on pathological and physiological quality and growth of rice IR 64 seedlings. The research objectives were (1) detection and identification of seed-borne pathogens of IR 64 rice, (2) testing Pseudomonas fluorescents P60 in inhibiting the in vitro growth of seed-borne pathogens colonies, (3) testing P. fluorescents P60 for pathological and physiological seed quality, and (4) testing P. fluorescents P60 on the growth of seedlings in the greenhouse. The results showed that some seed-borne pathogens can be found both on farmers’ IR 64 rice and factory’s; they were Aspergillus flavus, Alternaria padwickii, Pseudomonas glumae, and P. syringae. Application of P. flourescens P60 was able to inhibit the in vitrogrowth of colonies of all seed-borne pathogens, except P. syringae. Related to pathological quality, the effect of P. flourescens P60 on percentage of seed-borne pathogens attack did not significantly different from that of benomil but smaller than distilled water. On the physiological quality of seeds, treatment of P. flourescens P60 has the same effect with benomil and distilled water, with germination rate was more than 80%. In the greenhouse study,treatment of seed immersion time in P. flourescens P60 suspension showed that the effect of immersion time as long as15 minutes and 25 minutes on seedling height, root length, and seedling dry weightdid not significantly different. were. However, 25 minutes immersion time resulted in fresh seedling weight and root dry weight higher than that of 15 minutes immersion time.